2015
DOI: 10.1176/appi.ajp.2015.14121572
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Longitudinal Evaluation of the Effect of Deployment-Acquired Traumatic Brain Injury on Posttraumatic Stress and Related Disorders: Results From the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS)

Abstract: Objective Traumatic brain injury (TBI) is increasingly recognized as a risk factor for deleterious mental health and functional outcomes. The purpose of this study was to examine the strength and specificity of the association between deployment-acquired TBI and subsequent posttraumatic stress and related disorders among U.S. Army personnel. Method A prospective, longitudinal survey of soldiers in three Brigade Combat Teams was conducted 1–2 months prior to an average 10-month deployment to Afghanistan (T0),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 40 publications
4
97
0
Order By: Relevance
“…For this purpose we chose a dimensional measure of lifetime (“at its worst”) PTSD severity, a 6-item version (range: 0-24) of the PTSD Checklist (PCL) 64 that we have used in other published Army STARRS research. 65 Among European Americans rs11085374 was significantly associated with lifetime PCL-6 severity in NSS1 (p-value=0.007) and NSS2 (p-value <0.001), but not PPDS (p-value=0.82). Among African Americans rs159572 was significantly associated with lifetime PCL-6 severity in NSS1 (p-value=0.002) and NSS2 (p-value=0.028) but not PPDS (p-value=0.419).…”
Section: Resultsmentioning
confidence: 92%
“…For this purpose we chose a dimensional measure of lifetime (“at its worst”) PTSD severity, a 6-item version (range: 0-24) of the PTSD Checklist (PCL) 64 that we have used in other published Army STARRS research. 65 Among European Americans rs11085374 was significantly associated with lifetime PCL-6 severity in NSS1 (p-value=0.007) and NSS2 (p-value <0.001), but not PPDS (p-value=0.82). Among African Americans rs159572 was significantly associated with lifetime PCL-6 severity in NSS1 (p-value=0.002) and NSS2 (p-value=0.028) but not PPDS (p-value=0.419).…”
Section: Resultsmentioning
confidence: 92%
“…2014; Rosellini et al . 2015; Stein et al . 2015) which have been associated with substantial morbidity and severe role impairment (Rosellini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported an increased incidence of post-traumatic stress disorder (PTSD) in active-duty service members (Hoge et al, 2008;Schneiderman et al 2008;Yurgil et al, 2014;Stein et al, 2015) and civilians (Bryant et al, 2009;Bryant et al, 2010) with a history of mild traumatic brain injury (mTBI). Amongst veterans who have been deployed to Iraq or Afghanistan, a history of mild TBI is associated with a 2.37 fold increase in the prevalence of PTSD (Schneiderman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst veterans who have been deployed to Iraq or Afghanistan, a history of mild TBI is associated with a 2.37 fold increase in the prevalence of PTSD (Schneiderman et al 2008). In civilian populations, the association between mTBI and PTSD is as high as 56% (Howlett and Stein, 2015). The frequent co-morbidity of these two conditions has fueled a growing interest in characterizing the pathophysiological mechanisms that would support an increased susceptibility to PTSD in individuals who sustained mTBI (Joseph and Masterson, 1999;Gil et al, 2005;Kennedy et al, 2007;Elder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%